Життєвий і творчий ужинок фундатора хліборобської науки та освіти (до 115-річчя члена-кореспондента НАН України Г. С. Кияка) - Бомба, М.Я.; Бомба, М.І.; Коць, С.Я. (Вісник НАН України, 2025)
Статтю присвячено пам’яті видатного українського вченого в галузі рослинництва, луківництва, землеробства і селекції, заслуженого діяча науки і техніки УРСР (1964), лауреата премії імені В.Я. Юр’єва АН УРСР (1970), доктора сільськогосподарських наук (1956), професора (1949), члена-кореспондента НАН України (1951) Григорія Степановича Кияка. The article is dedicated to the memory of the outstanding Ukrainian scientist in the field of crop cultivation, meadow management, agriculture and breeding, Honored Figure of Science and Technology of the Ukrainian SSR (1964), laureate of the V.Ya. Yuryev Prize of the Ukrainian SSR Academy of Sciences (1970), Doctor of Agricultural Sciences (1956), Professor (1949), Corresponding Member of the National Academy of Sciences of Ukraine (1951) Hryhoriy S. Kyyak.